Air entrainment and mixture distribution in Diesel sprays investigated by optical measurement techniques. (January 2018) - Riess, Sebastian; Weiss, Lukas; Peter, Andreas; Rezaei, Javad; Wensing, Michael
Mie scattering, Schlieren technique and Raman spectroscopy are used to analyse air entrainment and mixture distribution in sprays at Diesel engine-relevant ambient conditions. Mixture formation for Diesel, gas-to-liquid Diesel, biodiesel (rapeseed methyl ester) and ethanol is investigated. The utilization of different fuels leads to locally equal mass flow ratios of fuel and ambient gas in the spray. The air entrainment process is dominated by conservation of the total spray momentum flux. Shortly after nozzle exit, the amount of ambient gas in the spray is high enough to make it the dominating component of the flow. Already 7 mm after the nozzle exit, the mass flow of ambient gas equals the mass flow of fuel. Also, the local mixture distribution in the spray – investigated by means of Raman spectroscopy – is fuel independent. Different physical properties of the fuels do (nearly) not influence the air entrainment and macroscopic mixture formation process, as the differences and the amount of fuel are too small to have a significant effect. Injection pressure and the resulting momentum flux are the dominating parameters of mixture formation. Because of the magnitude of the ambient gas content, the spray can be regarded as a gas jet.